2015
DOI: 10.1149/2.0631504jes
|View full text |Cite
|
Sign up to set email alerts
|

The Contamination Mechanism and Behavior of Amide Bond Containing Organic Contaminant on PEMFC

Abstract: This paper presents a study of the effects of an organic contaminant containing an amide bond (-CONH-), ε-caprolactam, on polymer electrolyte membrane fuel cells (PEMFCs). The ε-caprolactam has been detected in leachates from polyphthalamide materials that are being considered for use as balance-of-plant structural materials for PEMFCs. Contamination effects from ε-caprolactam in Nafion membranes are shown to be controlled by temperature. A possible explanation of the temperature effect is the endothermic ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…46 The concentration of O 2 in the catalyst layer is eliminated in Equation 3, as it was assumed constant throughout the experiment. 29,37 The reaction rate is assumed to be a 1.5 order with respect to the proton concentration as proposed previously. 47 δ is the catalyst layer thickness assumed equal to 2.5 and 10 μm for 0.1 and 0.4 mg/cm 2 respectively.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The concentration of O 2 in the catalyst layer is eliminated in Equation 3, as it was assumed constant throughout the experiment. 29,37 The reaction rate is assumed to be a 1.5 order with respect to the proton concentration as proposed previously. 47 δ is the catalyst layer thickness assumed equal to 2.5 and 10 μm for 0.1 and 0.4 mg/cm 2 respectively.…”
Section: Model Descriptionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] These results showed that despite the contamination caused by fuel and air side impurities that can effect only the catalyst (e.g., CO) or the membrane (e.g. metal cations), organic contaminants (e.g., those from BOP materials) can have severe effects on the catalyst, ionomer and membrane at the same time.…”
mentioning
confidence: 99%
“…Gas chromatography -mass spectrometry (GC-MS) was used to characterize the undoped (i.e., analyte-free) snow melt samples (Figure 4), with all samples showing peaks in the chromatograms corresponding to long-chain alkanes [43] and amides [44] that are typically found in fuel and other environmental contamination sources. Snow melt from Newport showed the lowest number of peaks, corresponding to the fewest organic contaminants, likely due to the sampling location selected (Newport sample from parking lot; Providence and Kingston samples from street).…”
Section: Gc-ms Experiments On Undoped Snow Samplesmentioning
confidence: 99%
“…Caprolactam adsorbates are also responsible for the activity loss. In addition, the aminocaproic acid hydrolysis produces a quaternary amine (−NH 3 + ) in acidic conditions, 28 which displaces the ionomer proton (ion exchange), decreases the water content, 48 diminishes the oxygen permeability 49,50 and increases the mass transport resistance. This explanation is consistent with the large decrease in diffusion-limited current for caprolactam (Fig.…”
Section: Effects Of Eg and Caprolactam Onmentioning
confidence: 99%
“…Both EG and caprolactam poison the ORR Pt/C, 28,32,33 but the H 2 O 2 yield has not been measured. In contrast to the slow ORR kinetics, the HOR kinetics on Pt/C catalysts is so fast that the cell voltage losses are negligible even for notably low Pt loadings.…”
mentioning
confidence: 99%